Adolescent exposure to violence and adult outcomes: results from the National Youth Survey Family Study - Menard, Scott W. (Lexington Books, 2021)
Adolescent exposure to violence -- Study design and sample characteristics -- Distribution of adolescent exposure to violence and adult outcomes -- Adolescent exposure to violence and adult socioeconomic statuses -- Adolescent exposure to violence and adult mental health -- Adolescent exposure to violence and adult substance use -- Adolescent exposure to violence and adult general violence: victimization and perpetration -- Adolescent exposure to violence and adult intimate partner violence: victimization and perpetration -- Adolescent exposure to violence and adult outcomes: implications for theory and practice.